Ansietas pada Lansia: Prevalensi, Faktor Penanda, dan Penanganannya - Raymond R. Tjandrawinata (PT Dexa Medica, 2026)
Anxiety in older adults is a prevalent mental health issue, yet it is frequently underrecognized due to the overlap symptoms with physical illnesses and age-related psychosocial changes. This article reviews the global prevalence, key risk markers,and evidence-based management approaches. Numerous studies indicate that anxiety in older adults is associated with chronic medical conditions (including pain), functional gastrointestinal disorders such as irritable bowel syndrome (IBS),low level of physical activity, and unhealthy dietary patterns. Evidence regarding direct association between serum vitamin D levels and anxiety in older adults remains inconsistent; however, emerging evidence suggests an indirect associationmediated through the role of vitamin D in gastrointestinal health and inflammatory process. Management of anxiety in older adults is recommended to follow a biopsychosocial approach, prioritizing psychological interventions such as cognitive behavioral therapy (CBT) and lifestyle modification, and selective pharmacotherapy reserved for moderate to severe cases.